Green Governance - One Solution for two problems? Climate change and economic shocks: risk perceptions and coping strategies in China, India and Bangladesh - Anja Senz; Dieter Reinhardt (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2010)
This collection of papers is based on an international workshop held in the summer of 2009 at the University of Duisburg-Essen. It brings together different perceptions regarding China, India and Bangladesh as they face the risks and crises of climate change and economic shocks like the recent global financial crisis. The papers reflect assumptions concerning the concept of Risk Society and discuss the extent to which Sustainable Development and the rather new concepts of Green Governance, Green Economy and the New Great Deal offer avenues for transforming risk societies into risk-avoiding and riskresistant societies and states. On the basis of these concepts, the current situation in China, India and Bangladesh is described, including the coping strategies which have been implemented so far. Contents: Tobias Debiel / Thomas Heberer: Preface - - - Anja Senz / Dieter Reinhardt: Introduction: Crisis Perception and Green Governance in Comparative Perspective: Questions, Concerns and Format of the Publication - - - Karen Shire: Risks as a Research Topic - Concepts and Methods - - - Chen Yugang: Measure for Meeting Challenges of Climate Change - a Chinese Perspective - - - Yang Long: Potential Instability Caused by the Financial Crisis - Measures Taken by the Chinese State - - - Anja Senz: Green Governance and Sustainable Development in China: Two Problems - One Solution? - - - Dinoo Anna Mathew: Climate Change in India with Special Reference to Women - - - Ash Narain Roy: Coping with Climate Change and Financial Crisis - the Indian Narrative - - - Dalem Barman: Climate Change and Security: A South Asian Perspective - - - Dil Rowshan: Anthropogenic Intervention in Natural Eco-Systems and Climate Change Adaptation in Bangladesh - - - Özlem Ipiv / Dieter Reinhardt: Sustainable Green Investments and Policies in Bangladesh: Two problems - One Solution? - - - Dieter Reinhardt / Anja Senz: Conclusions: Risks, the Green New Deal, and Green Governance - Lessons from South and East Asia
Keywords: 330; green governance; risk perception; climate change; financial crises; sustainable development; green new deal; green jobs; implementation; civil society; donor policies; China; India; Bangladesh